2003
DOI: 10.1128/jb.185.24.7291-7296.2003
|View full text |Cite
|
Sign up to set email alerts
|

ColonialDifferentiation in Streptomyces coelicolor Depends on Translation of a SpecificCodon within the adpA Gene

Abstract: We identified adpA as an araC-like regulatory gene needed for colonial morphogenesis in Streptomyces coelicolor and showed that its activity depended on a unique TTA triplet corresponding to the leucyl-tRNA gene (bldA). These findings partially explained the dependence of aerial mycelium formation on a rare tRNA that is postulated to have developmental control functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 20 publications
9
86
0
Order By: Relevance
“…From the 145 genes that possess a TTA codon, 33 at least one, adpA (bldH), is required for sporulation on glucose-containing media. 34,35 This suggests that the ability of iron to promote development must act upstream of the adpA regulatory network. The failure of iron to recover actinorhodin production is readily explained by the presence of a TTA codon within the sequence of the pathwayspecific activator actII-ORF4 gene which is required for activation of actinorhodin biosynthesis, as well as in actII-ORF2 for actinorhodin export.…”
Section: S Coelicolor Bld Mutants Are Affected In Siderophore Biosynmentioning
confidence: 99%
“…From the 145 genes that possess a TTA codon, 33 at least one, adpA (bldH), is required for sporulation on glucose-containing media. 34,35 This suggests that the ability of iron to promote development must act upstream of the adpA regulatory network. The failure of iron to recover actinorhodin production is readily explained by the presence of a TTA codon within the sequence of the pathwayspecific activator actII-ORF4 gene which is required for activation of actinorhodin biosynthesis, as well as in actII-ORF2 for actinorhodin export.…”
Section: S Coelicolor Bld Mutants Are Affected In Siderophore Biosynmentioning
confidence: 99%
“…A search of the S. coelicolor genome using nrdS as the query revealed 10 ORFs sharing 48-34% sequence identity. One, SCO2792, is a close homologue of the Streptomyces griseus AdpA transcriptional regulator (84.4% identity between the gene products) (Ohnishi et al, 1999;Horinouchi, 2002) and has recently been shown to be necessary for normal S. coelicolor aerial mycelium formation: it is the bldH gene (Nguyen et al, 2003;Takano et al, 2003). A second, SCO7512, is a close homologue of the Streptomyces aureofaciens GapR regulator (89% identity between the gene products) (Sprusansky et al, 2001).…”
Section: The S Coelicolor Class Ia and Class II Rnr Transcription Unmentioning
confidence: 99%
“…Previously, a bioassay method based on the pigment production by S. coelicolor was developed as a convenient assay for some GBL molecules (15). When we applied S. venezuelae culture extracts harvested at different times to S. coelicolor indicator plates, several fractions (12,24,30,36, and 42 h) were observed to induce pigment production (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…1A) and the fact that ScbR2 shows ∼31% identity to ArpA of Streptomyces griseus-which was known to bind the promoter region of adpA to repress its transcription (22)-we also tested the binding of ScbR2 to the promoter of adpA (adpAp), the product of which is the master regulator of aerial hyphal production in S. coelicolor (23)(24)(25). Remarkably, binding between ScbR2 and adpAp was observed (Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation